“When they know that you are a sex worker, you will be the last person to be treated”: Perceptions and experiences of female sex workers in accessing HIV services in Uganda - Wanyenze, Rhoda K. (BMC Int Health Hum Rights, 2017)
BACKGROUND: HIV prevalence among female sex workers (FSWs) in high burden countries in sub-Saharan Africa varies between 24 and 72%, however their access to HIV services remains limited. This study explored FSWs’ perspectives of the barriers and opportunities to HIV service access in Uganda. METHODS: The cross-sectional qualitative study was conducted between October and December 2013. Twenty-four focus group discussions were conducted with 190 FSWs in 12 districts. Data were analysed using manifest content analysis, using Atlas.ti software, based on the socio-ecological model. RESULTS: FSWs indicated that HIV services were available and these included condoms, HIV testing and treatment, and management of sexually transmitted infections. However, access to HIV services was affected by several individual, societal, structural, and policy related barriers. Individual level factors included limited awareness of some prevention services, fears, and misconceptions while societal stigma was prominent. Structural and policy level barriers included inconvenient hours of operation of the clinics, inflexible facility based distribution of condoms, interuptions in the supply of condoms and other commodities, and limited package of services with virtually no access to lubricants, HIV pre- and post-exposure prophylaxis, and support following client perpetrated violence. Policies such as partner testing and involvement at antenatal care, and using only one facility for antiretroviral drug refills hindered HIV service uptake and retention in care. FSWs had major concerns with the quality of services especially discrimination and rude remarks from providers, denial or delay of services, and potential for breach of confidentiality. However, some FSWs reported positive experiences including interface with friendly providers and participated in formal and informal FSW groups, which supported them to access health services. CONCLUSION: Despite availability of services, FSWs faced major challenges in access to services. Comprehensive multilevel interventions targeting individual, societal, structural and policy level barriers are required to increase access to HIVservices among FSWs in Uganda. Policy and institutional adjustments should emphasize quality friendly services and expanding the package of services to meet the needs of FSWs.